Do hedge funds time market tail risk? Evidence from option‐implied tail risk. Issue 2 (6th November 2018) - Shin, Jung‐Soon; Kim, Minki; Oh, Dongjun; Kim, Tong Suk
Abstract: This paper focuses on an unexplored dimension of fund managers' timing ability: Market‐wide tail risk implied by information in options markets. Constructing the option‐implied tail risk, we investigate whether hedge fund managers can strategically time the tail risk through adjusting their exposure to changes of it. Using an extensive sample of equity‐oriented hedge funds, we find strong evidence of tail risk timing ability of hedge fund managers. Furthermore, tail risk timing ability brings significant economic value to investors. Top‐ranked funds outperform bottom‐ranked funds by 5–7% annually after adjusting for risk factors. Our results are robust to various robustness checks.